Performance comparison of medium access control schemes for IEEE 802.11 - Kabir, Amran B M Zohrul; Alam, Mahjabeen A.; Ahmed, Lubna; Sabah, Sanjida Hossain; Ferdous, Hasan Shahid (© 2012 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 18th Asia-Pacific Conference on Communications: "Green and Smart Communications for IT Innovation", APCC 2012; Jeju Island; South Korea; 15 October 2012 through 17 October 2012 [© 2012 IEEE ] The conference paper's definite version is available at: http://doi.org/10.1109/APCC.2012.6388275